“Integrating Generative AI and Blockchain in Cloud-Based Collaboration Systems: Transforming Organisational Innovation and Transparency.” - Athar Javed Ali (Journal of Informatics Education and Research, 2025)
The rapid convergence of emerging technologies such as Generative Artificial Intelligence (GenAI), Blockchain, and Cloud Computing is redefining organisational structures, innovation processes, and managerial practices. This study explores the integration of Generative AI and Blockchain within cloud-based collaboration systems and examines their collective impact on organisational innovation, transparency, and managerial productivity. Generative AI enhances creativity, decision-making, and automation in collaborative environments, while Blockchain ensures data integrity, security, and trust across decentralised teams. When combined within a cloud ecosystem, these technologies enable intelligent, transparent, and efficient workflows that transform how organisations innovate and manage operations. The research aims to analyse the synergistic potential of these technologies in enhancing collaboration, fostering innovation, and improving organisational governance. Using a mixed-method approach—comprising survey analysis, case studies, and expert interviews—this study investigates the adoption challenges, implementation frameworks, and performance outcomes associated with AI-Blockchain-cloud integration. The findings are expected to provide actionable insights for managers, educators, and policymakers to design technology-enabled strategies that promote transparency, innovation, and sustainable productivity. This research contributes to the evolving discourse on digital transformation and positions the AI-Blockchain-Cloud triad as a foundation for next-generation organisational excellence.